2011
DOI: 10.1002/apj.636
|View full text |Cite
|
Sign up to set email alerts
|

Biomass char as a fuel for internal combustion engines

Abstract: Second generation liquid biofuels from lignocellulosic feedstocks are part of a suite of solutions to peak oil and a safe climate economy. Biofuels have technological advantages over electrification for applications with minimal refuelling or recharging options such as air travel, shipping, agriculture and low or intermittent frequency trucking and rail. We examined a fuel production concept combining slow pyrolysis chars and superfine commutation. Char is micronised and suspended in diesel or water to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This analysis did however identify that the ash present involved molecules containing calcium, potassium, and silicon, with some type of oxide being the most probable form. These are all common types of elemental ash found in biomass [17].…”
Section: Particle Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…This analysis did however identify that the ash present involved molecules containing calcium, potassium, and silicon, with some type of oxide being the most probable form. These are all common types of elemental ash found in biomass [17].…”
Section: Particle Analysismentioning
confidence: 98%
“…Biomass derived charcoal ash studied by Ellem and Mulligan [17] were found to contain mostly silicon (SiO 2 ), aluminum (Al 2 O 3 ), iron (Fe 2 O 3 ), calcium (CaO), magnesium (MgO), sodium (NaO 2 ), potassium (K 2 O), and phosphorus (P 2 O 5 ). It was noted that mechanical separation and leaching would be effective in removing the majority of ashes within biomass charcoals.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a carbon-rich material which originates from biomass being heated under oxygen-deprived conditions [1]. The properties of biochar allow for it to have several applications such as soil fertilizers, gas adsorbents and biofuels [2]. However, research on the suitability of these applications is still fairly recent, and more research is required to better understand this material.…”
Section: Introductionmentioning
confidence: 99%
“…Slow pyrolysis, usually using a temperature range between 350 and 800°C at slow heating rates (i.e. between 10 to 50°C/min) has been shown to produce a high-carbon, energy-dense solid char product which optimises char yield [1, [2], [7]. It has been shown that chemical pre-treatment of SCB can further enhance yields of char [8, [9].…”
Section: Introductionmentioning
confidence: 99%
“…However the energy requirements of refining bio-oil produced by pyrolysis were not included in the study. Ellem and Mulligan [6] concluded that pyrolysis of lignicellulosic biomass to char/gas product was more energy efficient than a biomass-to-liquid (BTL) process route. Furthermore they contended that the char could be processed to char-water fuel (CWF) and/or char-hydrocarbon fuel (CHF) which are suitable for use in ship, rail and other transport fuel applications.…”
Section: Introductionmentioning
confidence: 99%